2020
DOI: 10.3389/fgene.2020.00027
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Prognosis-Related lncRNAs and Genes in Gastric Cancer

Abstract: Gastric cancer is a common malignant tumor with high occurrence and recurrence and is the leading cause of death worldwide. However, the prognostic value of protein-coding and non-coding RNAs in stage III gastric cancer has not been systematically analyzed. In this study, using TCGA data, we identified 585 long noncoding RNAs (lncRNAs) and 927 protein-coding genes (PCGs) correlated with the overall survival rate of gastric cancer. Functional enrichment analysis revealed that the prognostic genes positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Gene set enrichment analysis revealed that gene body methylation could affect GC prognosis by regulating the neuroactive ligand-receptor interaction pathway, which has been also enriched for a number of long noncoding RNAs associated with OS of GC in a prior study 34 .…”
Section: Discussionmentioning
confidence: 91%
“…Gene set enrichment analysis revealed that gene body methylation could affect GC prognosis by regulating the neuroactive ligand-receptor interaction pathway, which has been also enriched for a number of long noncoding RNAs associated with OS of GC in a prior study 34 .…”
Section: Discussionmentioning
confidence: 91%
“…Wang et al found that abnormal expression of CD4 T cell subsets in peripheral blood of patients with ovarian cancer and an imbalance of Th1/Th2 and Treg/Th17 provide a basis for clinical immunotherapy of ovarian cancer [ 33 ]. In addition, Su et al identified lncRNAs and genes related to the prognosis of gastric cancer and showed that prognostic genes positively related to mortality were enriched in the CAM signaling pathway by performing a functional enrichment analysis [ 34 ]. Furthermore, Talia et al showed that GPER levels are related to metastasis and premigration genes belonging to the CAM signaling pathway in breast cancer [ 35 ], which further suggested that T cell-related genes may be related to the progression of liver cancer via Th1- and Th2-cell differentiation and CAM signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Gene set enrichment analysis revealed that gene body methylation could affect GC prognosis by regulating the neuroactive ligand-receptor interaction pathway [ 35 ], which has been also enriched for a number of long noncoding RNAs associated with OS of GC in a prior study [ 36 ]. Moreover, this pathway has also been enriched for differentially methylated genes between tumor and normal tissue of GC [ 37 ], indicating a significant role in both carcinogenesis and prognosis of GC.…”
Section: Discussionmentioning
confidence: 99%